Pengaruh Pengungkapan Sustainability Report Terhadap Kinerja Keuangan Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021 - Kurniadi, Dwifan; Effendy, Lukman; Isnaini, Zuhrotul (Fakultas Ekonomi dan Bisnis Unram, 2024)
The aim of this research is to empirically prove the influence of sustainability disclosures on the financial performance of mining companies listed on the IDX in 2019-2021. In this research, there are 3 independent variables tested, namely disclosure of economic performance, disclosure of social performance, and disclosure of environmental performance, while the dependent variable in this research is the company's financial performance which is measured using return on assets (ROA). The results of this research prove that disclosure of economic and social performance has no effect on the company's financial performance, while disclosure of environmental performance has an effect on the company's financial performance.